2022
DOI: 10.1002/ctpp.202200060
|View full text |Cite
|
Sign up to set email alerts
|

Study of the energy deposition of helicon plasmas driven by machine learning algorithms

Abstract: To find a fast and reliable way predicting the energy deposition of helicon plasmas, this work focuses on machine learning algorithms. Data generation model and the distribution property of the source data are studied, then the classical algorithms and deep neural network (DNN) are built, and these algorithms are studied to test the performance on the energy deposition datasets. Both decision tree classifier (DTC) and support vector machine (SVM) find the electron temperature is the noise feature, and when it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In the field of fusion plasma, several studies applying ML to a plasma ion source were reported [7][8][9]. The optimization studies of plasma density in helicon plasmas were also reported [10][11][12]. In these cases, algorithms such as the deep neural network, decision tree classifier and support vector machine have been applied.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of fusion plasma, several studies applying ML to a plasma ion source were reported [7][8][9]. The optimization studies of plasma density in helicon plasmas were also reported [10][11][12]. In these cases, algorithms such as the deep neural network, decision tree classifier and support vector machine have been applied.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in Narita et al, [9] a neural network is used to compute diffusive and non-diffusive transport parameters of tokamak fusion plasmas. Cheng et al [10] compare different machine-learning algorithms for predicting properties of helicon plasmas and conclude that their deep neural networks outperform other approaches.Neural networks have very fast response times, which opens up the possibility of using them for real-time control or online monitoring diagnostic settings. Tang et al [11] describe the implementation of a recurrent neural network as a disruption predictor into a control system intended to gracefully shut down the device before a damaging disruption can occur.…”
mentioning
confidence: 99%
“…Similarly, in Narita et al, [ 9 ] a neural network is used to compute diffusive and non‐diffusive transport parameters of tokamak fusion plasmas. Cheng et al [ 10 ] compare different machine‐learning algorithms for predicting properties of helicon plasmas and conclude that their deep neural networks outperform other approaches.…”
mentioning
confidence: 99%